PENGARUH PEMBELAJARAN MENGGUNAKKAN LKS INKUIRI TERINTEGRASI GENERIK SAINS (ITGS) TERHADAP HASIL BELAJAR FISIKA DITINJAU DARI MOTIVASI BERPRESTASI SISWA DI SMAN 1 AIKMEL - Muhammad Nasir; Ahmad Harjono; Nyoman Sridana (Jurnal Penelitian Pendidikan IPA, 2015)
The aim of this study was to evaluate difference of influence between inquiry integrated by science generic (IIBSG) student’s work sheet and experiment verification (EV) student’s work sheet learning on students’s phisycs learning outcomes, difference of influence between high and low achievement motivation level on students’s phisycs learning outcomes, and interaction between student’s work sheet and achievement motivation on students’s phisycs learning outcomes. Method of this research was experimental method with a 2x2 faktorial design. Data analyzed with two-way ANOVA. The conclution of this study include there was difference of influence between IIBSG student’s work sheet and EV student’s work sheet  learning on students’s phisycs learning outcomes, there was difference influence between high and low achievement motivation level on students’s phisycs learning outcomes, and there was no interaction between student’s work sheet learning and achievement motivation on students’s phisycs learning outcomes.Keywords: IIBSG student’s work sheet, achievement motivation, and student’s phisycs learning outcomes